Strategic Financial Management - Hill, Alan (R.A.Hill & Ventus Publishing, 2012)
"In a world of geo-political, social and economic uncertainty, strategic financial management is in a process of change. This requires a reassessment of the fundamental assumptions that cut across the traditional boundaries of the subject. Read this book and you will not only appreciate the major components of contemporary finance but also find the subject more accessible for future reference. "